Keanekaragaman Bintang Laut (Asteroidea) di Pantai Awang Kabupaten Lombok Tengah - Khairunnisah, Khairunnisah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This research aims to determine the diversity index of sea stars at Awang Beach, Central Lombok Regency. Starfish play an important role in the lives of living creatures. However, the existence of Starfish in each region is increasingly experiencing damage due to pollution and human activities. The type of research used is comparative descriptive research. Data collection techniques are in the form of direct observation and documentation. Based on the research results, it was found that there were five types of Starfish found in the waters of Awang Beach, Central Lombok Regency, including: Protoreaster nodus, Linckia leavigata, Archaster typhicus, Culcita novaeguineae, and Henricia leviuscula. Sampling was carried out at three station points, namely station I, station II and station III, using the quadrant transect method. The research results showed that the starfish diversity index at the three station points was 0.1590 in the low category.